2013
DOI: 10.1111/bjh.12333
|View full text |Cite
|
Sign up to set email alerts
|

Immature dendritic cells in multiple myeloma are prone to osteoclast‐like differentiation through interleukin‐17A stimulation

Abstract: SummaryInterleukin 17A (IL17A), a cytokine involved in allergy, inflammation and osteoclastogenesis, was investigated in multiple myeloma (MM) to assess its role in the osteoclast (OC)-like activity of marrow immature dendritic cells (iDCs). Comparing nine MM patients with control subjects affected by monoclonal gammopathy of undetermined significance, we found high IL17A expression in the marrow plasma of MM patients in parallel with its deposits within the stromal matrix. Increased expression of the IL17A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…In addition to the correlation with the extent of bone disease, 17 it has been recently reported that primary immature dendritic cells in MM are prone to osteoclast-like trans-differentiation after IL-17 stimulation. 24 Other roles have been ascribed to IL-17, such as promotion of MM cell growth/survival, which is supported by the expression of the IL-17 receptor on MM cell lines and primary tumors, 15,25 and inhibition of immune cell functions. 15 However, no direct correlation between Th17 cell numbers and disease prognosis and/or severity has been provided.…”
Section: Th17 Cells In MMmentioning
confidence: 99%
“…In addition to the correlation with the extent of bone disease, 17 it has been recently reported that primary immature dendritic cells in MM are prone to osteoclast-like trans-differentiation after IL-17 stimulation. 24 Other roles have been ascribed to IL-17, such as promotion of MM cell growth/survival, which is supported by the expression of the IL-17 receptor on MM cell lines and primary tumors, 15,25 and inhibition of immune cell functions. 15 However, no direct correlation between Th17 cell numbers and disease prognosis and/or severity has been provided.…”
Section: Th17 Cells In MMmentioning
confidence: 99%
“…21 Similarly, in multiple myeloma, IL-17A stimulates immature DCs to differentiate into osteoclast-like cells. 22 Evidence to date suggests that maturation of DCs might attenuate their differentiation into osteoclasts, but this area requires further investigation. 23 DCs are a heterogeneous cell lineage that includes various subtypes, such as CD11c + CD4 + cells, CD11c + CD8 + cells and CD11c + CD4 − CD8 − cells, and it remains to be determined whether a unique subset of immature DCs function as osteoclast precursors.…”
Section: Pathological Osteoclastogenesismentioning
confidence: 99%
“…However, given that IL-17A targeting drugs are still only in preclinical development for applications in LCH [85], the precise function of this cytokine in the disease needs to be elucidated to define the molecular pathways involved in the osteoclast-like transdifferentiation of dendritic cells. This phenomenon has been well established in other malignancies; we ourselves reported it in multiple myeloma, in which it is dependent on the activation of the receptor activator for nuclear factor kB (RANK)/RANKL, CD47/thrombospondin-1, and, overall, IL-17A/IL-17A receptor axes [86][87][88]. However, definite evidence in LCH is still lacking.…”
Section: Perturbations Of the Lch Microenvironmentmentioning
confidence: 74%